1976
DOI: 10.1172/jci108331
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E. An inhibitor of the platelet release reaction.

Abstract: A B S T R A C T Formation of lipid peroxides rises sharply when platelets undergo the release reaction. In this study the in vitro effect of vitamin E on platelet aggregation was investigated. a-Tocopherol, an antioxidant of known inhibitory action on lipid peroxidation, was added to platelet suspensions in concentrations up to 1.5 mM. A dose-dependent reduction in platelet aggregation was observed, with complete inhibition of the secondary wave of aggregation at > 0.9 mM atocopherol. The inhibitory effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
4

Year Published

1977
1977
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(77 citation statements)
references
References 25 publications
(19 reference statements)
4
68
1
4
Order By: Relevance
“…The serum level in smokers increased from 8.8±0.7 ,ug/ml at baseline to 20.6±2.9 ,g/ml after vitamin E. A similar increase (10.5±1.6-22.7±1.9 ,Ag/ml) was seen in nonsmokers. Serum vitamin E levels (baseline and supplemented) did not differ significantly between smokers and nonsmokers (P > 0.1, both comparisons), and are consistent with previously reported values (42)(43)(44).…”
Section: Resultssupporting
confidence: 91%
“…The serum level in smokers increased from 8.8±0.7 ,ug/ml at baseline to 20.6±2.9 ,g/ml after vitamin E. A similar increase (10.5±1.6-22.7±1.9 ,Ag/ml) was seen in nonsmokers. Serum vitamin E levels (baseline and supplemented) did not differ significantly between smokers and nonsmokers (P > 0.1, both comparisons), and are consistent with previously reported values (42)(43)(44).…”
Section: Resultssupporting
confidence: 91%
“…48 Several studies have shown that the antioxidant ␣-tocopherol inhibits platelet aggregation. 31,49,50 Nitrosothiols have also been shown to inhibit platelet aggregation. 24,51 Antioxidant flavonoids in tea may also inhibit platelet aggregation by a number of mechanisms.…”
Section: Duffy Et Al Tea Effects On Platelet Aggregationmentioning
confidence: 99%
“…It has an antioxidation function, and activates actions of tissue cells of living animals, such as hormone secretory cells and embryo cells4,5,11), and so it has been used for prophylaxis and therapy of reproductive disturbance in domestic animals and poultry2, 3,7,8).…”
mentioning
confidence: 99%